2000
DOI: 10.1111/1467-8624.00124
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model of Emotion Processes and Cognition in Social Information Processing

Abstract: Literature on the contributions of social cognitive and emotion processes to children's social competence is reviewed and interpreted in the context of an integrated model of emotion processes and cognition in social information processing. Neurophysiological and functional evidence for the centrality of emotion processes in personal-social decision making is reviewed. Crick and Dodge's model is presented as a cognitive model of social decision making, and a revised model is proposed into which emotion process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

70
1,059
4
46

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,134 publications
(1,179 citation statements)
references
References 46 publications
70
1,059
4
46
Order By: Relevance
“…Such steps would commonly involve interpreting cues, clarifying goals, generating alternative responses, selecting and implementing a specific response, and evaluating the outcome. Social problem solving is often assessed by asking children to reflect on and answer questions about hypothetical social dilemmas (Dodge, Laird, Lochman, & Zelli, 2002 Recent theorists have recognized that social information processing depends on other cognitive and affective factors and have incorporated into their models such constructs as language pragmatics, executive function, and emotion regulation (Dodge et al, 2002;Guralnick, 1999;Lemerise & Arsenio, 2000). The latter variables are typically treated as stable individual characteristics (i.e., "latent knowledge" per Dodge et al, 2002; "foundation processes" per Guralnick, 1999).…”
Section: Model Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such steps would commonly involve interpreting cues, clarifying goals, generating alternative responses, selecting and implementing a specific response, and evaluating the outcome. Social problem solving is often assessed by asking children to reflect on and answer questions about hypothetical social dilemmas (Dodge, Laird, Lochman, & Zelli, 2002 Recent theorists have recognized that social information processing depends on other cognitive and affective factors and have incorporated into their models such constructs as language pragmatics, executive function, and emotion regulation (Dodge et al, 2002;Guralnick, 1999;Lemerise & Arsenio, 2000). The latter variables are typically treated as stable individual characteristics (i.e., "latent knowledge" per Dodge et al, 2002; "foundation processes" per Guralnick, 1999).…”
Section: Model Componentsmentioning
confidence: 99%
“…Specifically, the cognitive-executive and socialaffective functions in Figure 1 reflect aspects of social information processing that are linked to a network of specific brain regions (Adolphs, 2001;Grady & Keightley, 2002). At the same time, they also represent the stable individual characteristics (i.e., latent knowledge or foundation processes) described in recent models of social competence (Dodge et al, 2002;Guralnick, 1999;Lemerise & Arsenio, 2000).Social cognitive neuroscience also links research on children's social development to the study of childhood brain disorder. Many childhood brain disorders involve insults to the largely anterior brain regions implicated in social information processing.…”
mentioning
confidence: 99%
“…Emotion was measured in terms of arousal reactivity by Williams, Lochman, Phillips, and Barry (2003) who found that moderately aggressive boys exhibited increased heart rate and increased hostile attributions when a threat was introduced. In a test of Lemerise and Arsenio's (2000) theoretical model including emotion, hostile attributions, and aggression, boys' report of their own anger was related positively to their hostile attributions, as well as to their aggression (Orobio de Castro, Merk, Koops, Veerman, & Bosch, 2005). In this same study, boys' interpretation of a peer as appearing angry was related to increased hostile attributions.…”
Section: Hostile Attributions and Emotionmentioning
confidence: 63%
“…As emotion relates to step 2 (interpretation), the authors suggested that the interpretation of hostility could lead to fear or anger, which could further result in preemptive processing, rather than deliberative information-processing. More recent research has suggested that emotion should be an integrated part of the social informationprocessing model because children can come into a social interaction in pre-existing emotional states or with schemas that include affective components from past interactions, in addition to the emotion generated within the social interaction itself (Lemerise & Arsenio, 2000). The emotional cues of a peer in a social situation, as well as schemas, might be particularly influential on the attribution step.…”
Section: Hostile Attributions and Emotionmentioning
confidence: 99%
See 1 more Smart Citation